Différenciation et Articulation dans les Systèmes d'Enseignement Supérieur en Afrique : Une étude de douze pays africains. - Subotzky, G. (George); Afeti, George (World Bank Group, 2008)
This title explores an area of tertiary education that is currently understudied; this is the extent and nature of differentiation and articulation in African tertiary education systems. The overall finding is that the binary system is dominant, characterised by universities and polytechnics as distinct types of institutions. Differentiation is clearly evident in Africa. However, though varied in nature and extent, the differentiation is mostly horizontal as opposed to vertical. Articulation, on the other hand, seems to be in its infancy as some universities, in their admission requirements, do not recognise polytechnic qualifications, and mobility between similar institution types is rare. While national policy, market forces, institutional reforms, industry, and regional initiatives drive differentiation, resource constraints, isomorphism, governance and funding structures, and the absence of size and shape debates act as inhibitors. Demand for access appears the only driver for articulation while national policies, internal governance structures, and industry/labour market inhibit its growth. The study concludes that knowledge of both differentiation and articulation in African tertiary systems is still scanty. Therefore, this exploratory study should lead to more work aimed at anchoring differentiation and articulation within national tertiary education systems.